Biotreatment of industrial effluents - Doble, Mukesh; Kruthiventi, Anil Kumar (Burlington, MA : Elsevier Butterworth-Heinemann, 2005)
With increasing government regulation of pollution, as well as willingness to levy punitive fines for transgressions, treatment of industrial waste is a important subject. This book is a single source of information on treatment procedures using biochemical means for all types of solid, liquid and gaseous contaminants generated by various chemical and allied industries. This book is intended for practicing environmental engineers and technologists from any industry as well as researchers and professors. The topics covered include the treatment of gaseous, liquid and solid waste from a large number of chemical and allied industries that include dye stuff, chemical, alcohol, food processing, pesticide, pharmaceuticals, paint etc. Information on aerobic and anaerobic reactors and modeling and simulation of waste treatment systems are also discussed. * Compares chemical and biochemical means of industrial waste treatment * Provides details of technology (i.e. reactors, operating conditions etc) with regard to the biochemistry aspects. * Can be used as a teaching aid for graduate courses and a reference material by practicing environmental scientists and engineers. * Researchers can extract synergy between treatment procedures and various effluents.
Environmental disasters -- Aerobic and anaerobic bioreactors -- Mathematical models -- Treatment of waste from organic chemical industries -- Chlorinated hydrocarbons and aromatics, and dioxins -- Fluoride removal -- Biodegradation of pesticides -- Degradation of polymers -- Degradation of dyes -- Textile effluent -- Tannery effluent -- Treatment of waste from metal processing and electrochemical industries -- Semiconductor waste treatment -- Waste from nuclear plants -- Cyanide waste -- Treatment of waste from food and dairy industries -- Sugar and distillery waste -- Paper and pulp -- Paint industries -- Pharmaceuticals -- Hospital waste treatment -- Treatment of waste from explosives industries -- Petroleum hydrocarbon pollution -- Biodesulfurization -- Treatment of solid waste -- Treatment of municipal waste -- Groundwater decontamination and treatment -- Denitrification -- Gaseous pollutants and volatile organics.
Includes bibliographical references and index.
Keywords: Factory and trade waste -- Purification; Waste products -- Environmental aspects; Bioremediation; Electronic books